How Bio-sciences could trigger a Green Revolution in Africa - Juma, C. (International Livestock Research Institute, 2011)
Calestous Juma, of Harvard University, talks with clarity and humour about the hopeful future that he sees for Africa as the use of bioscience grows in the African agricultural sector. He predicts that once started, African development will be faster than Chinese development since Africa has access to decades more globally generated knowledge. This 40-minute keynote presentation was given by Juma at the International Livestock Research Institute in Nairobi in March 2011. The occasion was the official launch of a regional Bio-Innovate Program, during which Juma introduced his newly published book The New Harvest – Agricultural Innovation In Africa (Oxford University Press 2010).